Implementasi Model Seci dalam Meningkatkan Learning Organization di Industri Multifinance: Studi Kasus FIFGroup Central Lampung - Djerica Fitria Adinda S Raya; Habiburahman Habiburahman; Haninun Haninun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The increasingly dynamic development of the multifinance industry requires companies to possess strong adaptive capabilities and sustainable organizational learning. In this context, knowledge management has become a strategic factor in enhancing organizational competitiveness and performance. One of the widely applied knowledge management frameworks is the SECI model (Socialization, Externalization, Combination, and Internalization), which explains the process of knowledge conversion between tacit and explicit knowledge. This study aims to analyze the effect of the SECI model on learning organization at FIFGROUP Central Lampung. This study employs a quantitative approach using Partial Least Square–based Structural Equation Modeling (SEM-PLS). Data were collected through questionnaires distributed to employees of FIFGROUP Central Lampung using a five-point Likert scale. Data analysis was conducted using SmartPLS software to examine validity, reliability, and causal relationships among the research variables.The results indicate that the SECI model has a positive and significant effect on learning organization simultaneously. Partially, the dimensions of socialization, externalization, combination, and internalization each have a positive effect on learning organization, with varying levels of contribution. These findings suggest that the effectiveness of the knowledge conversion process plays a crucial role in building an adaptive and sustainable learning organization within the multifinance industry.This study is expected to contribute theoretically to the development of knowledge management and learning organization literature, as well as provide practical implications for the management of FIFGROUP Central Lampung in formulating strategies to strengthen organizational learning based on the SECI model.